Optimisation of sprinting performance in running, cycling and speed skating - van Ingen Schenau, G. J.; de Koning, J. J.; de Groot, G. (Sports Medicine, 1994)
Sprinting performances rely strongly on a fast acceleration at the start of a sprint and on the capacity to maintain a high velocity in the phase following the start. Simulations based on a model developed in which the generation of metabolic power is related to the mechanical destinations of power showed that for short-lasting sprinting events, the best pacing strategy is an all out effort, even if this strategy causes a strong reduction of the velocity at the end of the race. Even pacing strategies should only be used in exercises lasting longer than 80 to 100 seconds.